MAIN SOURCES OF FINANCING THE GREEN ECONOMY IN UZBEKISTAN - Sotvoldiev Alisher , Abdumukhtarovich (THE INNOVATION ECONOMY, 2025)
The article examines key aspects of green economy financing in Uzbekistan, including public investment, international grants, private capital and the use of green bonds. The emphasis is on the analysis of financial support mechanisms and their impact on sustainable development. The authors propose to strengthen state support, develop private financing, introduce innovative technologies and expand international cooperation for the further implementation of the principles of a green economy in the national policy of Uzbekistan. The article emphasizes the importance of an integrated approach to achieving sustainable development goals and improving economic efficiency.